Relative length of the gut of some freshwater fishes of West Bengal in relation to food and feeding habits - Gupta, M Das (Indian Journal of Fisheries, 2011)
Relative length of the gut (R.L.G.) and the quantity of vegetable and animal matter in the gut content of fifty five species of commonly available freshwater fishes of West Bengal has been determined. The R.L.G. value varied from 0.33 in Wallago attu to 9.42 in Labeo gonius. The R.L.G. value had a close relationship with the nature of gut content. The average R.L.G. value was 0.70 in carnivorous fishes, 4.77 in herbivorous, 1.37 in omnivorous and 3.70 in planktivorous fishes.